2005
DOI: 10.1086/426510
|View full text |Cite
|
Sign up to set email alerts
|

Treponema pallidumStrain‐Specific Differences in Neuroinvasion and Clinical Phenotype in a Rabbit Model

Abstract: There are particularly neuroinvasive T. pallidum strains, and the clinical phenotype of infection varies with infecting strain. This information could ultimately be used to identify patients at increased risk for neuroinvasion and, thus, at risk for neurosyphilis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 14 publications
2
40
0
2
Order By: Relevance
“…The absence of T. pallidum DNA in 60% of the brains at this time point insinuates that the Nichols strain is not as neuroinvasive as previously thought. This finding is in agreement with a previous study by Tantalo et al (33) showing that the Nichols strain was present in the brain of only 2/8 rabbits studied and monitored over a 3-month period and, when present, was rapidly cleared. The lower DNA copy numbers in the organs studied, in contrast to the very high numbers in whole blood or plasma, suggest that replication in these tissues begins at a later point and perhaps in lower numbers following bacteremic spread from the infected testes.…”
Section: Discussionsupporting
confidence: 93%
“…The absence of T. pallidum DNA in 60% of the brains at this time point insinuates that the Nichols strain is not as neuroinvasive as previously thought. This finding is in agreement with a previous study by Tantalo et al (33) showing that the Nichols strain was present in the brain of only 2/8 rabbits studied and monitored over a 3-month period and, when present, was rapidly cleared. The lower DNA copy numbers in the organs studied, in contrast to the very high numbers in whole blood or plasma, suggest that replication in these tissues begins at a later point and perhaps in lower numbers following bacteremic spread from the infected testes.…”
Section: Discussionsupporting
confidence: 93%
“…Investigators believed that the course of events after neuroinvasion was, at least in part, determined by the host response to infection. For example, several investigators noted a correlation between the severity of the secondary syphilis skin rash and identification of CSF abnormalities in early syphilis [51]. Merritt et al [19] noted that symptomatic NS was rarely seen in individuals who had experienced severe skin manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical descriptions from the pre-antibiotic era (137) and studies in the rabbit infection model suggest that some strains are more prone to neuroinvasion (138). A recent study of T. pallidum showed that patients infected with strain type 14d/f had a higher rate of neurosyphilis compared with patients infected with other strain types (135).…”
Section: Molecular Strain Typing Of T Pallidummentioning
confidence: 99%